2015
DOI: 10.1589/jpts.27.989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise performance by elderly women on balance ability and muscle function

Abstract: [Purpose] The aim of this study was to investigate the effect of an exercise intervention on the balance ability and muscle function of elderly women. [Subjects] The subjects were randomly divided into a control group (n=10) and an exercise group (n=10). [Methods] The subjects participated in an elastic band exercise program lasting for 8 weeks, exercising for 40 minutes, four days a week with resting terms of 60 sec. Subjects used a band corresponding to 60% of the strength of the color band with which repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
(9 reference statements)
0
23
0
1
Order By: Relevance
“…Therefore, identifying interventions that improving physical function represents one of the primary goals of geriatric medicine. To date, the therapeutic intervention attempting to improve muscle function has got progressive exercise training [13]. there is evidence of a beneficial effect of progressive exercise training on muscle strength and gait speed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying interventions that improving physical function represents one of the primary goals of geriatric medicine. To date, the therapeutic intervention attempting to improve muscle function has got progressive exercise training [13]. there is evidence of a beneficial effect of progressive exercise training on muscle strength and gait speed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…26 Resistance band exercises are helpful in healthy and frail older adults. 27,28 Such exercises have been found to enhance muscle strength and endurance; 29,30 improve balance, agility, and gait speed; 29,31,32 promote muscle hypertrophy; 33 and boost lower extremity function. 34 Furthermore, resistance band exercises have been reported to improve functional ability, 29 increase cardiovascular endurance, 29,31 increase flexibility and range of joint motion, 29,35 and enhance overall physical fitness of older adults.…”
mentioning
confidence: 99%
“…Other intervention study demonstrated that resistance exercise using elastic band is effectively improves physical fitness such as muscle function and balance ability in elderly women13 ) . And resistance exercise using elastic band are simple and economical, and have safety advantages13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Other intervention study demonstrated that resistance exercise using elastic band is effectively improves physical fitness such as muscle function and balance ability in elderly women13 ) . And resistance exercise using elastic band are simple and economical, and have safety advantages13 ) . In this study, resistance exercise was to use elastic bands, and health-related indicators such as blood pressure as well as body composition and physical fitness variables were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation